Behavior of CFRP-Confined Sand-Based Material Columns under Axial Compression - Guodong Li (MDPI AG, 2021)
This paper presents an innovative pumpable standing support designed for underground mines located in the arid and semi-arid deserts of the Gobi region with a shortage of water resources. The exterior shell of this pumpable standing support is made of carbon fiber-reinforced polymer (CFRP), while the infill material is a sand-based material (SBM). As the novel backfill material, SBM is the combination of high-water cementing material and desert sand. A series of experimental tests were conducted to obtain the mechanical response mechanism of this novel pumpable standing support under uniaxial compression. Test variables investigated in this research covered the water-to-powder ratio of the cementing material, the mixing amount of sand, and the thickness of the CFRP tube. Test results confirmed that the CFRP-confined SBM columns exhibited typical strain hardening behavior with the acceptable axial deformation. It was also demonstrated that using high-strength cementing material, a thicker CFRP tube, and a high mixing amount of sand effectively increased the bearing capacity of the CFRP-confined SBM column. Except for the exemplary structural behavior, the consumption of high-water cementing materials of the novel pumpable standing support is smaller than that of its counterparts made of pure cementing material, when specimens with the same mechanical performance are compared.